DIGITAL TRANSFORMATION AND AI INTEGRATION IN MODERN LANGUAGE TEACHING AND INTERPRETING PRACTICE - UROKOVA, Diyora (The Lingua Spectrum, 2025)
AI integration and digital transformation are reshaping language education and interpreting by providing adaptive learning systems, speech recognition, and computer-assisted tools that enhance personalized instruction, practice opportunities, and professional preparation. While these technologies improve efficiency and learner engagement, their effectiveness depends on informed human oversight, ethical use, and the educator’s or interpreter’s expertise to mediate AI-generated feedback and maintain pedagogical integrity.